PEREMPUAN SINGLE PARENT YANG BEKERJA DI RUANG PUBLIK UNTUK MEMENUHI NAFKAH KELUARGA : (Suatu Tinjauan Sosiologi Hukum Islam) - Moh Zakky; Wahyuni Wahyuni (Program Studi Perbandingan Mazhab, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2021)
This study discusses single parent women who work in public to fulfill family income; a sociological review of Islamic law with a study in Maninili Village, South Tinombo, Parigi Moutong. The results show that the factors of single parent women who work in public to meet family income consist of: first, the background factors which include internal factors, daily needs and children's education, and external factors, higher income. Second, the problem factors (problems faced) which include internal factors, economic problems and family problems, and external problems, social problems. Furthermore, a review of the sociology of Islamic law on single parent women who work in public to meet family income is explained in QS. Al-Baqarah (2): 233 which emphasizes the ability to work in public by obtaining salaries from other people. From the conclusions obtained, it is recommended that single parent women should be patient, trustful and never give up in facing life as a single parent by always thinking positively and ignoring the negative stigma from society that hinders their work to fulfill family income.